2019
DOI: 10.1007/s11031-019-09816-3
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between psychological need satisfaction and psychological need frustration within a work context: A variable and person-oriented approach

Abstract: A plethora of empirical data support a positive (or "brighter") pathway to optimal human functioning as specified within Basic Psychological Needs Theory (Ryan and Deci in Psychol Inq 11(4):319-33, 2000). Yet, far less is known about the negative (or "darker") pathway, a process evoking of human dysfunction and ill-being (cf. Vansteenkiste and Ryan in J Psychother Integr 23(3):263, 2013). Further, debate surrounds the independence and interplay between psychological need satisfaction and psychological need fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 49 publications
10
59
1
4
Order By: Relevance
“…Firstly, employees who show low behavioral trust (in terms of reliance and disclosure) lack a sense of volition and authenticity regarding their tasks (Ryan and Deci, 2017), they feel incapable of achieving valued outcomes, and they do not have close relationships with significant others (Deci and Ryan, 2000;Ryan and Deci, 2017;Rouse et al, 2020). The results showed that low autonomy satisfaction was associated with low reliance and low disclosure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, employees who show low behavioral trust (in terms of reliance and disclosure) lack a sense of volition and authenticity regarding their tasks (Ryan and Deci, 2017), they feel incapable of achieving valued outcomes, and they do not have close relationships with significant others (Deci and Ryan, 2000;Ryan and Deci, 2017;Rouse et al, 2020). The results showed that low autonomy satisfaction was associated with low reliance and low disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…When examining theoretical frameworks that contain dynamic and interactionistic within-person conceptualisations (Rouse et al, 2020), for our purpose, the person-centered approach is preferable to traditional variable-centered approaches because it recognizes that variables may not necessarily combine in identical ways for all types of individuals (Meyer et al, 2015;Meyer and Morin, 2016). Little is known about the combinations of trust dimensions and the associations thereof with psychological well-being, work engagement and intention to leave of employees.…”
Section: A Person-centered Approach To Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally validated in Dutch, English, Spanish, and Chinese, today a variety of translations and contextspecific adaptations are available, including validations in German (Heissel et al 2018), Japanese (Nishimura and Suzuki 2016), Italian (Costa et al 2018), Hebrew (Benita et al 2020), Turkish (Selvi and Bozo 2020), and Portuguese (Cordeiro et al 2016). It has also been adapted for specific contexts, including work (Rouse et al 2020;Schultz et al 2015), school (Vandenkerckhove 2019b), and volunteering, among others (see Appendix for an overview of different translations and adaptations).…”
Section: Theme 2: Which Costs Are Associated With Basic Psychologicalmentioning
confidence: 99%
“…Knowing as a counselor to which need profile an individual belongs may allow for more tailored interventions targeting one or more basic needs. Although some studies have identified profiles based only on need satisfaction scores (Earl et al 2019), two contributions in this special issue focused on the within-person patterning of both need satisfaction and need frustration in the domains of sport and physical education (Warburton et al 2020) and work (Rouse et al 2020). Various profiles were identified, with those being characterized by a stronger presence of need satisfaction and by an absence of need frustration yielding the most adaptive outcomes.…”
Section: Future Directionsmentioning
confidence: 99%